Tributação sobre lucros e agressividade tributária: um estudo no âmbito das empresas de capital aberto do Brasil - Silva, Jonas Ismael da (Universidade do Vale do Rio dos Sinos, 2025)
This study aims to analyze the effect of the aggressive taxation of Brazilian companies listed on the B3 stock exchange on investments, performance, and earnings management from 2010 to 2024. The deductive method was adopted, classifying the research as applied in nature, explanatory in objectives, documentary in procedures, and quantitative in approach to the problem. The population consists of companies listed on the B3, resulting in a sample of 293 companies from 2010 to 2024, totaling 2,713 observations. Data collection was carried out using the Economática® database, with the data initially processed in Excel spreadsheets using the variables of the econometric models. The data were then entered into the RStudio software to run the model equations and subsequently analyzed using the Hausman test for the general data and the Ordinary Least Squares (OLS) method for economic sectors and governance levels. The analysis by economic sector revealed that some sectors showed significance in explaining tax aggressiveness, and governance levels also revealed significant effects. It is concluded that the models explain the relationship with profitability, operating margin, and market value, but do not explain deferred taxes. Among the economic sectors, Information Technology, Cyclical Consumption, and Public Utilities stood out, showing consistent negative impacts on performance and return indicators; while, among the governance levels, Level 3, Bovespa Mais, and the Traditional level stood out, showing distinct effects on performance and deferred taxes.
Keywords: Planejamento tributário; Agressividade tributária; Gerenciamento de resultados; Tax planning; Tax aggressiveness; Earnings management; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis